2018
DOI: 10.17159/2309-8775/2018/v60n1a1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of free-flow conditions on multilane intercity highways under heterogeneous traffic conditions

Abstract: Master of Technology (MTech) from the National Institute of Technology Kurukshetra (NIT) in 2012 on the topic "Effect of fly ash on the CBR value of different soils". He is currently a PhD research scholar at the Indian Institute of Technology (IIT) Roorkee, India, and is working on the topic "Operational performance measures for intercity roads". He has published more than ten research papers in reputed international journals and conference proceedings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Following Miller’s (1961) proposal [ 17 ], later adopted by Boora et al, (2018) [ 43 ], we can utilize these differences in distributions to identify the range of speed differences in which the frequencies of the non-free-moving vehicle sub-sample exceed those of the free-moving vehicle one. If the speed difference distribution of sub-sample 2 exceeds that of sub-sample 3 within a certain interval, then there are more vehicles in sub-sample 2 with speed differences falling within that interval than there are free-moving vehicles in sub-sample 3.…”
Section: Results: Free-moving and Constrained Vehicles Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Following Miller’s (1961) proposal [ 17 ], later adopted by Boora et al, (2018) [ 43 ], we can utilize these differences in distributions to identify the range of speed differences in which the frequencies of the non-free-moving vehicle sub-sample exceed those of the free-moving vehicle one. If the speed difference distribution of sub-sample 2 exceeds that of sub-sample 3 within a certain interval, then there are more vehicles in sub-sample 2 with speed differences falling within that interval than there are free-moving vehicles in sub-sample 3.…”
Section: Results: Free-moving and Constrained Vehicles Analysismentioning
confidence: 99%
“…In these scenarios, the driver may maintain a specific following distance and speed that matches the vehicle in front of them. This can result in a platoon of vehicles with a more uniform speed and inter-vehicle spacing, known as following by choice or intentional platooning [ 10 , 43 ]. It is based on the driver’s autonomous decision and not on external factors, such as traffic congestion/interactions or overtaking impracticality/prohibition.…”
Section: Methods: Characterization Of Free-moving and Conditioned Veh...mentioning
confidence: 99%
See 1 more Smart Citation
“…Thirdly, the data contains a high level of unobserved heterogeneity, which may affect identifying the exact contributing factors, so the models accounting for heterogeneity in data analysis merit further deep investigation. Finally, the coupling effect of multiple factors on the severity of MME crashes was not focused on in this study, such as the existence of tunnels and bridges (Sun et al 2020), so one of the greatest future challenges is to unpack which combinations of factors produce the greatest risks (Boora et al 2018;Santos et al 2021), such as driver's risk driving behaviour and sharp curves coincided, and traffic flow and weather conditions interacted, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Bang et al [5], however, stated that free-flow speed should be determined for unobstructed vehicles based on the definition of the vehicles with headway to the nearest vehicle in front of more than 8 s and no recent or immediate meeting with a vehicle in the opposing direction. Nevertheless, according to Boora et al [6], for heterogeneous traffic conditions on multilane highways, a gap is more suitable to use than a headway as a gap does not vary due to vehicle length. A new measure called "Speed Difference" was introduced by Boora et al and was found to be suitable for identifying the free-flow conditions.…”
Section: Introductionmentioning
confidence: 99%